THE ISLAMIC NARRATIVE OF BASIC HUMAN DEVELOPMENT INDICATORS OF UNDP - Muhammad Omer Rafique; Dr. Muhammad Akram Hureri; Dr. Hafiz Atif Iqbal; Qurat ul Ayn; Dr. Khushbakhat Alia; Muhammad Abdullah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
The individual and collective ambitions of all Muslims should be aligned with the utmost guidance given to them in the form of the Quran and Sunnah. It is significant for Muslims to learn and apply the Islamic perspective on the three most important development indicators stated by the United Nations Human Development in its Report 1990 and detailed in the recent SDGs (Sustainable Development Goals). These are Health, literacy, and a better standard of living. The study aims to highlight the Islamic narrative on these three aspects of life as an indicator of development. The method of the present study is a qualitative grounded theory. For this purpose, data was gathered from the study population which consisted of the Quran and authentic Ahadith. The study concluded that Human Development is one of the core targets of Islam. It establishes a system of worship that advances them towards real development which not only comprises the three indicators (longevity, knowledge, and decent living) but ads and advocates for one more essential ingredient, which is spirituality and strength of a human soul, to form a revolutionary human in this world and in the hereafter.